Population abundance of red spider mite in different vegetables along with its spatial distribution and chemical control in brinjal (Solanum melongena L.) (Bangladesh Journal of Agricultural Research, 2012)
Population abundance of red spider mite, Tetranychus urticae Koch., was studied in cucmber, ribbed gourd, bitter gourd, snake gourd, aroids and teasle gourd and efficacy of four new acaricides were tested against this pest in brinjal at the farmers field of Norsingdi during 2009-2010. At the same time, the spatial distribution of this pest in brinjal crop was also studied. Results indicated that all the surveyed vegetables except bitter gourd were attacked by the mite with varying levels of infestation. However, the highest mite population per leaf was observed in brinjal (32.27) which was followed by cucumber (16.08) and teasle gourd (7.2). Mites were most densely populated in the lower canopy region in the brinjal plant. Among the tested acaricides, Lakad 1.8 EC (Abamectin) provided the highest (83.4%) reduction of mite population over control, although the other acaricides also gave good control of this pest. Bangladesh J. Agril. Res. 37(3): 399-404, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12083